(untitled) (International Journal of Biology and Chemistry, 2019)
Development of new effective drugs with myeloid poiesis stimulating activity is highly relevant due to the increase in the number of patients with hematological disorders. Acquired hematological diseases are associated with unbalanced and inadequate nutrition, chronic blood loss, living in ecologically disadvantaged areas, extreme physical activity, use of cytostatic and cytotoxic drugs, chronic stress, and other. Azaheterocyclic compounds are perspective for search of new effective myeloid poiesis stimulating drugs. The incentive for this search was the manifestation of myeloid poiesis stimulating activity by azaheterocycles drug Prosidol (Propionylphenylethoxyethylpyperidine) in clinical practice. On the model cyclophosphamide myeloid depression high myeloid poiesis stimulating activity showed that compound of the dimethyl ether of P-(4-methoxyphenyl)-1-(4-phenylpiperazine) methyl] - phosphonic acid in laboratory coding of BIV-95. In a series of experiments showed myeloid poiesis stimulating activity at the level of comparison compound (2, 3, 5, 6-tetrahydro-6-phenylimidazo [2, 1-b] thiazole hydrochloride (Levamizol drug). The erythropoiesis stimulating activity exceeded the activity of the comparison compounds. The thrombocytopoiesis stimulating activity was at the level of the comparison compounds. Leukopoiesis stimulating activity also was slightly higher than the activity of Levamizol drug. Recovery of granulocytic and agranulocytic leukocyte were no violations of immunoregulatory index in leukogram blood. The test compound is the dimethyl ether of P-(4-methoxyphenyl)-1-(4-phenylpiperazine) methyl]-phosphinic acid compound under the laboratory coding BIV-95 had low toxicity.